Sample preparation for Raman microspectroscopy - Jahn, I. J.; Lehniger, L.; Weber, K.; Cialla-May, Dana; Popp, Jürgen (Physical Sciences Review, 2020)
Raman spectroscopy and its variants allow for the investigation of a wide range of biological and biomedical samples, i. e. tissue sections, single cells and small molecules. The obtained information is on a molecular level. By making use of databases and chemometrical approaches, the chemical composition of complex samples can also be defined. The measurement procedure is straight forward, however most often sample preparation protocols must be implemented. While pure samples, such as high purity powders or highly concentrated chemicals in aqueous solutions, can be directly measured without any prior sample purification step, samples of biological origin, such as tissue sections, pathogens in suspension or biofluids, food and beverages often require pre-processing steps prior to Raman measurements. In this book chapter, different strategies for handling and processing various sample matrices for a subsequent Raman microspectroscopic analysis were introduced illustrating the high potential of this promising technique for life science and medical applications. The presented methods range from standalone techniques, such as filtration, centrifugation or immunocapture to innovative platform approaches which will be exemplary addressed. Therefore, the reader will be introduced to methods that will simplify the complexity of the matrix in which the targeted molecular species are present allowing direct Raman measurements with bench top or portable setups.
CRIS-Team Scopus Importer:2023-04-20
Keywords: microfluidics; optical tweezers; pathogen; Raman spectroscopy; sample clean-up; tissue